Conjunctive use methods in the management of surface water and ground water resources of a river basin - a review / G. Jagmohan Das and Ashfaque Jafari - G. Jagmohan, Das; Jafari, Ashfaque (Universiti Teknologi MARA, Sarawak, 2003)
Most of the river valley projects experience problems like water logging and salinity leading to reduced crop yields and ecological degradation.